Characteristics and trends of globally registered glioma clinical trials in the past 16 years - Xiaofang He; Wenbin Zhao; Jianwen Huang; Jia Xu; Shaoqing Niu; Qun Zhang; Nu Zhang; Huawei Jin; Guoping Shen (Therapeutic Advances in Neurological Disorders, 2022)
Background: Advancement in the treatment of glioma has been vacant since temozolomide has proved its therapeutic value in glioblastoma in 2005. Aim: To help investigators understand the landscape of glioma clinical research, we analyzed the characteristics and trends of globally registered glioma trials in the past decades. Methods: This is a cross-sectional analysis of glioma trials registered on ClinicalTrials.gov between January 2006 and December 2021. Characteristics regarding phase, enrollment number, study design and type, funding source, tumor site, pathology, patient status, age of population, trial purpose, and participating country were abstracted, and chronological shifts were analyzed. Results: There were 1531 registered glioma trials involved 58 participating countries. The trial purpose concerning surgery, radiotherapy, chemotherapy, targeted therapy, tumor-treating fields, immunotherapy, other antiglioma therapy and non-antiglioma research trial accounts for 3.5%, 6.5%, 9.5%, 28.9%, 2.0%, 16.4%, 12.5%, and 20.6%, respectively. In the past 16 years, the numbers of chemotherapy and targeted therapy trials declined; tumor-treating fields and immune checkpoint inhibitor application trials sprang at the latter half period; Immunotherapy, other antiglioma therapy and non-antiglioma research trials escalated (all above p trend  < 0.005). The trend also showed the phased trials registered diminishingly and that the trials which focused on glioblastoma registered incrementally (those two p trend  < 0.05). Among 784 drug therapy trials, it was included 45 cytotoxic drugs, 186 targeted drugs, 19 immune checkpoint inhibitors, 78 other drugs, and five immunomodulatory drugs. Two trials belonged to Bayesian adaptive randomized design. By the end of December 2021, 309 trials had publications. Only everolimus and tumor-treating fields exhibited meaningful survival benefit in specific glioma patients in phase 3 trials. Conclusion: Meaningful effective treatments regarding drugs or methods for glioma were difficult to be found. Bayesian adaptive platform trials may accelerate clinical research in glioma. Development of novel treatment modalities for glioma is still challenged.